Small towns, big challenges: Does rurality influence Safe Drinking Water Act compliance?. Issue 1 (7th January 2019) - Marcillo, Cristina E.; Krometis, Leigh‐Anne H.
Abstract : Despite amendments and financial investment, noncompliance with the Safe Drinking Water Act persists in portions of the United States. This study hypothesizes that rural and urban U.S. residents are exposed to different patterns of drinking water violations and contaminants. Violations ( n > 9, 500) for 1, 133 Virginia community water systems (CWSs) from 1999 to 2016 were analyzed to (1) evaluate the effects of size and rurality on compliance, (2) identify patterns in contaminant prevalence, and (3) identify gaps in consumer protection. Results indicate that very small CWSs had significantly more monitoring and reporting (MR) violations than large systems, while medium CWSs had significantly more maximum contaminant‐level violations. Isolated rural area CWSs had significantly high MR noncompliance compared with town and urban centers. This study highlights chronic MR noncompliance across rural regions of the state, which may mask consumer health concerns. Further work directly linking health records and noncompliance is recommended to quantify this risk.